2008
DOI: 10.1007/s10900-008-9122-8
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge About Breastfeeding Among a Group of Primary Care Physicians and Residents in Puerto Rico

Abstract: Physicians have an essential role in promoting, protecting, and supporting breastfeeding as the ideal method of infant feeding. They are in an important position to promote breastfeeding but report difficulty in advising mothers with lactation problems. The purpose of this study is to assess knowledge about breastfeeding among primary care physicians and residents and identify potential barriers to its promotion. One hundred seventy-seven residents and physicians answered an anonymous questionnaire. The partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 4 publications
2
21
0
2
Order By: Relevance
“…Similar influences by physicians have been reported in a study in Turkey [11]. A study in Puerto Rico showed that as many as 26% of primary care physicians did not encourage exclusive breastfeeding [12]. A study in France showed that trained primary care physicians were effective in increasing breastfeeding duration [13].…”
Section: Discussionsupporting
confidence: 53%
“…Similar influences by physicians have been reported in a study in Turkey [11]. A study in Puerto Rico showed that as many as 26% of primary care physicians did not encourage exclusive breastfeeding [12]. A study in France showed that trained primary care physicians were effective in increasing breastfeeding duration [13].…”
Section: Discussionsupporting
confidence: 53%
“…A large cohort study undertaken in rural Ghana concluded that 22% of neonatal deaths could be prevented if all infants were put to the breast within the first hour of birth [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Despite such endorsements, studies have shown that physician knowledge on breastfeeding is far from ideal [3-8], as they receive relatively little formal training on breastfeeding [5], and often fail to follow evidence-based medicine (EBM) guidelines [9]. However, it can be difficult for physicians to keep up-to-date with the high volume of constantly changing, sometimes conflicting, information.…”
Section: Introductionmentioning
confidence: 99%